Homogeneously dispersed CeO2 nanoparticles on exfoliated hexaniobate nanosheets. (December 2017) - Marques, Thalles M.F.; Strayer, Megan E.; Ghosh, Anupama; Silva, Alexandre; Ferreira, Odair P.; Fujisawa, Kazunori; Alves da Cunha, Jose R.; Abreu, Guilherme J.P.; Terrones, Mauricio; Mallouk, Thomas E.; Viana, Bartolomeu C.
Abstract: Hexaniobate nanosheets derived from the parent compound K4 Nb6 O17 have been decorated with CeO2 nanoparticles by ion exchange with aqueous cerium (IV) solution. Very homogeneous CeO2 nanoparticle decoration of the hexaniobate sheets can be achieved by this method and the resulting composites may absorb visible light. HRTEM images show that ∼3.0 nm diameter CeO2 nanoparticles adhere to hexaniobate nanosheets that are exfoliated and then restacked prior to Ce deposition. The interfacial interaction between CeO2 nanoparticles and nanosheets would be due to an electrostatic attraction mechanism. Raman and XRD measurements have given strong evidence that CeO2 nanoparticles have fluorite structure. EDS, FTIR and XPS results suggest almost complete exchange of TBA + and K + by Ce 4+ . Cerium ion exchange on the acid exchanged parent compound, H2.9 K1.1 Nb6 O17, revealed that the extent of Ce ion exchange is much greater in case of nanosheets, which may be rationalized by the larger surface area available after exfoliation. XPS measurements show that the ratio of Ce 4+ /Ce 3+ is around 4.4, in agreement with the formation of fluorite structure (CeO2 ). Thus, these CeO2 nanoparticle/nanosheet composites may be useful for catalytic processes. Graphical abstract: Highlights: Mechanism of CeO2 nanoparticles growth onto hexaniobate nanosheets. Hybrid nanosystem – CeO2 -hexaniobate.